Respuesta :

Simplifying

2x2y + 3x2 + 4y + 3x2y + 2y = 0

Reorder the terms:

3x2 + 2x2y + 3x2y + 4y + 2y = 0

Combine like terms: 2x2y + 3x2y = 5x2y

3x2 + 5x2y + 4y + 2y = 0

Combine like terms: 4y + 2y = 6y

3x2 + 5x2y + 6y = 0

Solving

3x2 + 5x2y + 6y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6y' to each side of the equation.

3x2 + 5x2y + 6y + -6y = 0 + -6y

Combine like terms: 6y + -6y = 0

3x2 + 5x2y + 0 = 0 + -6y

3x2 + 5x2y = 0 + -6y

Remove the zero:

3x2 + 5x2y = -6y

Combine like terms: -6y + 6y = 0

3x2 + 5x2y + 6y = 0

The solution to this equation could not be determined.